Wdrażanie controllingowej koncepcji zarządzania w przedsiębiorstwie państwowym - próba oceny efektywności - Węgrzyn, Adam (Implementation of Controlling-Based Management Conception in a State-Owned Enterprise - the Attempt of Efficiency Evaluation, 2006)
The following research paper presents the attempt to evaluate the efficiency of the recent process of implementation of Controlling-based Management Concept in the Gas Transmission Operator "Gaz-System" - Division in Wroclaw. It focuses mainly on the efficiency evaluation of the first completed stage of the process based on changes of the company's organizational culture as well as the on-going stage of implementation of the IT supportive devices, called IT stage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 526-534